A prospective, multicentre study of 6‐mm short implants in posterior alveolar bone supporting splinted crowns: A 5‐year follow‐up study. (30th March 2022) - Sui, Huiping; Tang, Zhihui; Zhang, Xiao; Wei, Diyuan; Meng, Huanxin; Han, Jie
Abstract: Aim: To evaluate the clinical and radiographic outcomes of 6‐mm short implants, placed in the posterior jaws and supporting splinted crowns, at 5 years after early loading. Materials and Methods: Forty‐five patients with 95 implants (diameter: 4 mm; length: 6 mm) were enrolled at three centres. Two to three implants were placed in either the maxillary or the mandibular posterior region in each patient and restored with screw‐retained splinted crowns at 6 weeks later. Clinical and radiographic outcomes were evaluated at implant placement, at loading, and at 6, 12, 24, 36, and 60 months after loading. Biological and mechanical complications were recorded. Marginal changes in bone level in relation to clinical parameters were evaluated using a generalized linear mixed model. Results: During the 5 years of follow‐up, the mean change in the marginal bone level (MBL) was 0.04 ± 0.14 mm. Four implants in four patients were lost before loading, one implant in one patient was lost at the 5‐year follow‐up, and two patients were lost to follow‐up. The survival and success rates were 88.4% (38/43) at the patient level. The incidence rates of peri‐implant mucositis and peri‐implantitis were 29.4% and 7.0%, respectively. The rate of technical complications was 14.0%. Conclusions: Over a 5‐year period, 6‐mm short implants supporting early loaded splinted crowns in maxillary or mandibular posterior regions showed stable MBLs and acceptable technical and biological complication rates.